2013
DOI: 10.1038/jhh.2013.101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supine versus sitting position on noninvasive assessment of aortic pressure waveform: a randomized cross-over study

Abstract: Biomarkers derived noninvasively from the aortic blood pressure (BP) waveform provide information regarding cardiovascular (CV) risk independently of brachial BP (bBP). Although body position has significant impact on the assessment of bBP, its effect on aortic hemodynamics remains unknown. This study investigated the changes in both brachial and aortic hemodynamics, between the supine and sitting position. In this randomized cross-over study, the bBP and the aortic pressure waveform were assessed after a 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
3
16
0
1
Order By: Relevance
“…Currently, both seated (with the wrist often below the heart level) and supine postures are accepted for radial waveform assessment, often providing different results [22,23], and especially when associated systemic hemodynamic changes are detected [24,25]. Our data are in keeping with the findings by Vrachatis et al [26], who reported that changes in distending pressure were responsible for the differences in HR-adjusted AIx and PP amplification between the seated and the supine position. This issue is of particular relevance in light of the recent commercial availability of devices enabling 24-h noninvasive central BP assessment, based on brachial or radial sensors for waveform assessment [27].…”
Section: Discussionsupporting
confidence: 88%
“…Currently, both seated (with the wrist often below the heart level) and supine postures are accepted for radial waveform assessment, often providing different results [22,23], and especially when associated systemic hemodynamic changes are detected [24,25]. Our data are in keeping with the findings by Vrachatis et al [26], who reported that changes in distending pressure were responsible for the differences in HR-adjusted AIx and PP amplification between the seated and the supine position. This issue is of particular relevance in light of the recent commercial availability of devices enabling 24-h noninvasive central BP assessment, based on brachial or radial sensors for waveform assessment [27].…”
Section: Discussionsupporting
confidence: 88%
“…Unlike the systolic peak of the arterial pulse, mean and diastolic pressures are relatively stable between the aorta and resistance arterioles (31). In addition, the use of peripheral PP to reflect changes in cerebral PP is supported by the observation of a strong correlation between posture-related changes in peripheral and central PP (50).…”
Section: Discussionmentioning
confidence: 99%
“…Several observations point to a need to examine within-beat pulsatile characteristics. Importantly, posture-related shifts in pulse pressure (PP) have been shown to be a function of changes in systolic and diastolic pressures, independent of mean pressure (50). Despite similar posture-induced changes in mean pressure, PP is reduced in young adults and maintained in older adults during standing (29).…”
mentioning
confidence: 99%
“…Applied on our study, based on AUC's, we noticed a slightly better predictive outcome with standing blood pressures instead of supine blood pressures. There is however some inconsistency concerning the influence of position on the blood pressure: lower supine blood pressures are reported as compared to sitting [1,28,29], but also higher values have been observed [30] as well as no differences at all [31,32]. These conflicting results may relate to different populations or other methods of measurement.…”
Section: Discussionmentioning
confidence: 99%